The Genetic Variability of Thalassaemia. A Family Study. Issue 4 (December 1973) - Torre, E. De La; Svarch, E.; Colombo, B.
Abstract : Two step-brothers, homozygotes for β-thalassaemia, have been studied. One of them showed the characteristics of Cooley's anaemia, whereas the other was almost symptomless. The existence of two different β-thalassaemic genes is discussed in relation to the haematological and clinical findings.